Analisis Pemenuhan Hak Anak Korban Eksploitasi Seksual (Suatu Hal yang Utopis Dalam Penegakan Hukum di Indonesia) - Anisa Wulandari; R. Rahaditya (Dinasti Research, 2024)
Sexual exploitation is a form of trafficking with the focus and purpose of obtaining financial value or profit from victims who are forced to engage in sexual acts. This legal article focuses on dissecting and examining how positive legal arrangements regarding sexual exploitation provisions and how forms of protection can be carried out by the state and the forms of responsibility that will be imposed on perpetrators of criminal acts. Based on the District Court Decision Number 566/Pid.Sus/2020/PN.Mgl, which is the main object of writing this article, it shows the weak form of protection for children as victims of trafficking crimes. Therefore, this normative juridical legal article will focus on reasoning and reviewing applicable laws and regulations accompanied by an analysis of reading book materials used in literature studies. Thus, in the end, this journal article is able to answer the positive legal order regarding sexual exploitation contained in the Trafficking in Persons Act, the Sexual Violence Act and describe the protection of the rights of child victims in accordance with the Child Protection Law